Frost - James, Kathryn (London: Hodder Children's, 2013)
The forest beyond the mist is the home of the Elven: rarely glimpsed, misunderstood. Enigmatic, beautiful Evan belongs here, and Nell is captivated by him. But Evan's world is now frozen and only Nell can help Evan save it. Last time Nell went into the mist it was to rescue her sister. This time she'll have to go farther than the forest, deep into the frozen wastes beyond, where a deadly lake of ice and an ancient adversary await her. Suggested level: secondary